Mycobacterium abscessus pulmonary infection complicated with vertebral osteomyelitis in a heart transplant recipient: case report and literature review. Issue 3 (19th May 2015) - Silva, J.T.; López‐Medrano, F.; Fernández‐Ruiz, M.; San‐Juan, R.; Ruiz‐Cano, M.J.; Delgado, J.F.; Aguado, J.M.
Abstract Infections produced by Mycobacterium abscessus are emerging in immunosuppressed patients, such as solid organ transplant recipients. We report the first case, to our knowledge, of a vertebral osteomyelitis caused by M. abscessus in a heart transplant recipient, and review the risk factors, manifestations, and therapeutic approaches to this uncommon disease.